2022
DOI: 10.1507/endocrj.ej21-0630
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal paragangliomas with immunohistochemical deficiency of succinate dehydrogenase subunit B

Abstract: Recent progress in paraganglioma (PGL) revealed genotype-phenotype relationship, especially succinate dehydrogenase complex subunit B (SDHB) gene mutation-related to the extra-adrenal origin and metastasis. SDHBimmunohistochemistry can detect all types of SDH-subunit mutations, and is a useful tool to detect SDH-mutation tumors. PGLs usually occur along with sympathetic, and parasympathetic chains, however, colorectal paraganglioma is extremely rare. We have experienced one sigmoid colon PGL and one rectal PGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The immunohistochemical results were similar to those in our case; all cases were positive for neuroendocrine markers, and S-100 highlighted sustentacular cells. Furthermore, there are currently three reports of paraganglioma originating in the rectum, and we concluded that the microscopic morphological features and immunohistochemical results were similar to our case, with main organ-like nests ( 3 , 5 , 8 ). However, the cell proliferation activity in these three rectum-origin cases was high, and the index of Ki-67 was 20%, 41%, and 50%, respectively ( 3 , 5 , 8 ) Among the eight cases mentioned above, only three performed SDHB immunohistochemical staining and were diagnosed with SDHx-related paragangliomas.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The immunohistochemical results were similar to those in our case; all cases were positive for neuroendocrine markers, and S-100 highlighted sustentacular cells. Furthermore, there are currently three reports of paraganglioma originating in the rectum, and we concluded that the microscopic morphological features and immunohistochemical results were similar to our case, with main organ-like nests ( 3 , 5 , 8 ). However, the cell proliferation activity in these three rectum-origin cases was high, and the index of Ki-67 was 20%, 41%, and 50%, respectively ( 3 , 5 , 8 ) Among the eight cases mentioned above, only three performed SDHB immunohistochemical staining and were diagnosed with SDHx-related paragangliomas.…”
Section: Discussionsupporting
confidence: 86%
“…Review of the domestic and foreign literature showed that paragangliomas that occur in the gastrointestinal tract are very rare and more common in the stomach, and there are a few literature reports of origination in the rectum (5). Colonic paragangliomas are extremely rare, with only 4 cases having been reported in the literature (6)(7)(8)(9). The first case of colonic paraganglioma was reported by Yao et al in 1997 (7).…”
Section: Discussionmentioning
confidence: 99%
“…A pseudorosette pattern usually suggests immature tumors, which are mainly observed in pseudopapillary tumors of the pancreas and in some pituitary tumors [ 2 , 31 ]. Previously, a case of poorly differentiated colorectal paraganglioma exhibiting a pseudorosette pattern and demonstrating a negative result on SDHB immunostaining, suggesting a SDHB gene mutation, was reported [ 32 ]. Additionally, a case of intermediately differentiated PCC that was positive on SDHB immunostaining exhibited this pseudorosette pattern [ 33 ], suggesting the absence of a mutation in the SDHB gene, although target germline gene testing was not conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in SDHx subunits are associated with many tumors, including familial paraganglioma (PGL) [ 103 ], pheochromocytoma (PHEO) [ 104 ], gastric stromal tumors [ 105 ], renal cell carcinoma [ 106 ], pituitary adenoma [ 107 ], papillary thyroid carcinoma [ 108 ], pancreatic neuroendocrine tumor [ 109 ], and gastric and colorectal carcinoma [ 110 ]. There are increasing reports of the coexistence of PHEO/PGL and pituitary adenomas, which are referred to as 3PAS.…”
Section: Succinate: An Enhancer Of Tumorigenesis Through Modulating T...mentioning
confidence: 99%